The Development of Urban Logistics in Public Transport Systems in The Light of the COVID-19 Pandemic - The Case of Poland - Ewa PUZIO (Communications of International Proceedings, 2023)
Highly urbanized cities are important engines of the economy, being places of meeting, creativity and innovation, and centers of services provided to their surrounding areas. Due to their population density, cities have the potential to save energy and transform towards a low-carbon economy. Cities are also places where problems such as unemployment, segregation and poverty are concentrated. More than half of the world's population lives in cities, and this number will increase even further. The rapid development of urban areas is becoming an increasing challenge for city engineers and planners. An important area is the planning of contemporary transport and logistics systems in terms of the flow of passengers and goods in urban areas. The article deals with the issue of innovative solutions in the field of urban logistics in public transport. The aim of the article is to present innovative logistic solutions supporting the transport system of urbanized urban areas. A detailed review of Polish and foreign scientific literature was carried out. The practical implementations in the field of city logistics, improving the functioning of transport systems in cities, were verified and assessed. Novel methods of managing public transport supported by intelligent transport systems were proposed.
Keywords: city logistics; urban transport systems; public transport.